"'Indian' doesn't exclude me": An interview with Eunice de Souza. Issue 1 (4th March 2017) - Nerlekar, Anjali
Abstract: As poet, anthologist, journalist and teacher, Eunice de Souza has imprinted the Bombay reader's consciousness over several decades with her concise and strong creative expression. In this interview undertaken at her residence in Santa Cruz in 2011 and 2015, the poet talks about her early years in Pune and Bombay, her dark childhood after the early loss of her father, and the impact it had on her work. Eunice de Souza also discusses the role of small presses in creating a space for writers, and her own point of view as a woman as well as a poet in English – and the way these are connected, in turn, to questions of national identity.